Pharmacokinetic and pharmacodynamic integration and resistance analysis of cefquinome against Streptococcus uberis in vitro dynamic model - Li, Chongyang; Wang, Junli; Guo, Fanxi; Zhang, Fengyichi; Chen, Baochang; Wang, Zihan; Cao, Di; Yu, Zugong (Frontiers in Microbiology, 2025)
IntroductionStreptococcus uberis (S. uberis) is a major pathogen that causes acute clinical mastitis and its recurrent episodes in dairy cows.MethodsIn this study, a peristaltic pump one-compartment open model was established to investigate the relationship between the pharmacokinetic and pharmacodynamic (PK/PD) indices of cefquinome (CFQ) against S. uberis. Bactericidal effects of single high-dosage versus multiple low-dosage administrations within the same drug dosage and best-fit dosage were assessed.ResultsStatic time-killing curves showed that the population of S. uberis was not changed when the drug concentration was below 1 × MIC. The maximum antibacterial effect was observed at 24 h, when the concentration exceeded 2 × MIC, showing a reduction by 5.73 log10 (CFU/mL), and the maximum kill rate was 0.22 h−1. S. uberis were cleared at 120 h when the concentration was ≥1 mg/L within single high-dosage groups, except for the 0.28 and 0.5 mg/L groups. The multiple-dose groups decreased below 2.22 log10 (CFU/mL) at 48 h and increased to 9 log10 (CFU/mL) at 120 h, but the group of 0.25 mg/L (4, q24) increased at 144 h. As the frequency of administration increased, the lag time increased following a population decline. The correlation coefficients between AUC0-72h/MBC, %T > MBC, and the antibacterial effects were 0.90 and 0.99%, respectively. %T > MBC was the best-fit PK/PD parameter of CFQ against S. uberis. The MIC of S1–S5 strains ranged from 0.0156–0.0625 μg/mL, and biofilm formation ability increased.DiscussionIn conclusion, CFQ showed good efficacy and time-dependence. This study provides a reference for optimizing CFQ administration in S. uberis.